Pembentukan Wirausaha Muda melalui Inkubator Bisnis Kewirausahaan Universitas PGRI Palangka Raya - Asro Laelani Indrayanti; Arief Rahman Hakim; Yos Andi Tangkasiang; Perwira Jati Wicaksono; Robby Julianto; Daryana Daryana (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Alumni of High Education is expected to be not only job seekers but also job creators. The role of the business world in employment is enormous, both large businesses, medium businesses, and MSMEs. The absorption of labor by SMEs is far greater than others. However, the development of MSMEs is still hampered by several obstacles, including limited knowledge in the field of production technology, limitations in reading the market, marketing technology is always simple, not thinking about strategic plans both short and long term and others. Universitas PGRI Palangka Raya tries to play a role in increasing employment through the establishment of new entrepreneurs and technology-based through Business Incubator of Universitas PGRI Palangka Raya. The novelty of the approach developed in developing this Entrepreneurial Business Incubator is the application of Human Design to detect potential and weaknesses of tenants so that a business that is suitable for the tenant can be determined. The Human Design approach will help provide direction for tenants to start their own business. The selection of tenants starts from the Entrepreneurship Seminar, which is then followed by a one-week Entrepreneurship Training Bootcamp. During the Entrepreneurship Training Bootcamp, tenants will be shown their potential and weaknesses with the Human Design approach. After the Entrepreneurship Training Bootcamp, tenants are asked to perfect their business plans and are still given Entrepreneurship Coaching. Until the end of the first-year program, eight successful independent entrepreneurs have been formed.